(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2025)
In this brief study, I draw upon texts previously produced by myself and other scholars from earlier research, aiming to trace the paths of the "cassemireiros" who arrived in Maranhão. The intention is to offer data capable of providing an understanding of how the Cassimiro Coco puppet migrated from the Northeast to the Mid-North region, and, especially, how this puppet manages to remain present in the "toldas" (tent shows) of popular Maranhão artists.